In vitro and in vivo anti-diabetic effects of Marantodes pumilum and Rhinacanthus nasutus and their active compounds / Siti Hajar Adam - Siti Hajar , Adam (2018)
Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by insulin resistance and defective insulin secretion. The aims of DM treatment is to modulate insulin secretion and ameliorate insulin resistance, in order to protect the target organs from damage. Herbal medicines are used as an alternative treatment for DM, as they could have lesser side effects, compared to the currently available conventional drugs. Two tropical herbs i.e Marantodes pumilum (M. pumilum) and Rhinacanthus nasutus (R. nasutus) have been claimed to be helpful in the treatment of DM, however, their mechanisms of actions have yet to be fully identified. In this study, mechanisms underlying anti-diabetic effects of these herbs and their active compounds were investigated in vitro and in vivo. In the in vitro study, hexane, ethyl acetate, methanol, ethanol and aqueous extracts from leaves of M. pumilum and R. nasutus were tested for α-amylase and α-glucosidase inhibitory activity. Further, evaluation of their ability to enhance glucose uptake was identified by using dexamethasone-induced adipocyte cells, both in the basal and insulin-stimulated conditions. Meanwhile, in vivo study was performed using streptozotocin-nicotinamide-induced diabetic male rats where an aqueous extract of M. pumilum, naringin (a bioactive compound from M. pumilum) and Rhincanthin-C (bioactive compound from R. nasutus) were administered orally. Their effect on metabolic profiles and on the pancreas i.e. morphology, levels of oxidative stress, inflammation and apoptosis were identified. Results: In vitro screening of αamylase and α-glucosidase inhibitory activity showed that M. pumilum ethyl acetate extract and R. nasutus ethyl acetate and ethanolic extracts were able to inhibit both iv enzymes and only α-amylase enzyme activities, respectively. In vitro glucose uptake study showed ethyl acetate extract from both plants’ leaves was able to induce highest glucose uptake at basal and insulin-stimulated conditions. In the meantime, in vivo study showed an aqueous extract of M. pumilum, naringin and Rhinacanthin-C possess antihyperglycemic, anti-hyperlipidemic, insulin-secretagogue aa well as were able to ameliorate pancreatic damage as a result of oxidative stress, inflammation and apoptosis. The improvement in the metabolic profiles was evidenced from the restoration of near normal body weight, food and water intakes, fasting blood glucose, glycated hemoglobin (HbA1c), lipid levels and insulin secretion. Amelioration of pancreatic oxidative stress was evidenced from the reduced lipid peroxidation and the increased in anti-oxidative enzymes’ level including superoxide dismutase, glutathione peroxidase and catalase. Amelioration of pancreatic inflammation was evidenced by the decreased in NF-kB, IKκB, TNF-α and IL-1β levels while amelioration of apoptosis was evidenced by the decrease in caspase-3, caspase-9 and Bax levels. On the other hand, levels of antiinflammatory and anti-apoptosis marker Nrf-2 and Bcl levels in the pancreas increased, respectively. In addition, the morphology of pancreatic islets in diabetic rats improved following administration of these compounds, with naringin enhance the proliferation of the pancreas as indicated by high proliferative cell nuclear antigen (PCNA) levels. Both naringin and Rhinacanthin-Cwere able to stimulate GLUT-2 expression in the pancreas. In conclusions. M. pumilum and its active compound naringin and R. nasutus with its active compound, Rhinacanthin-C possess a wide range of anti-diabetic effects in which they can potentially be used in the treatment of DM.